CANS ANTENNA AMPLIFIER UTILYZATION COMPUTER-BASED NETWORK ACCESS POINT - Khalis Ali Mufattihul Rangga Saputra; Nenny Anggraini, SKom., MT (Jurnal Sistem Komputer, 2007)
Scientific writing is about the use of tin as an antenna amplifier in a network without cables based on the access point. Limited funds to set up a network, either using a cable or using a wireless antenna into the main factors using tin as a wireless antenna that can strengthen the wave from the receiving antenna (receiver) to the access point. Calculation can be an antenna that will be something that can not be ignored in order to obtain a good signal reinforcement.